The Application of Different Fertilizers and Depths in The Rearing of Seaweed Caulerpa racemosa Using a Concrete Tank - Mutiara Annisa Dewi; Moh. Awaludin Adam; Salnida Yuniarti Lumbessy; Raismin Kotta (Postgraduate, University of Mataram, 2024)
This study used a concrete tank to analyze the interaction between different fertilizers and depths in C. racemose seaweed rearing. This study was experimental, using a factorial Completely Randomized Design (CRD) consisting of 2 factors, namely fertilizer (P) and depth (K). The fertilizers consisted of NPK (P1) and sap (P2), and the depths (K) consisted of 5 cm (K1), 10 cm (K2), and 15 cm (K3). Each treatment was repeated 3 times, so we had 18 combined treatments. The study was done at the Cultivation Laboratory of the National Innovation Research Agency (BRIN), Lombok, Indonesia. Research procedures included preparing material and tools, rearing C. racemosa, and harvesting C. racemosa. Research parameters included final weight, final length, specific decline rate, and survival rate. Data were analyzed using ANOVA. The results showed that the interaction of different fertilizers and depths affected the final weight, specific decline rate, and survival rate of C. racemosa. Meanwhile, the final length of C. racemosa was only influenced by different fertilizers. The best treatment happened in the interaction of NPK fertilizer and a depth of 15 cm, which gave a survival rate of 89%, a final weight of 88.66 g, and a specific decline rate of -10.67%/day